A New Perspective on Liver Injury by Traditional Chinese Herbs Such As Polygonum multiflorum: The Geographical Area of Harvest As an Important Contributory Factor - Lin, Longfei; Li, Hui; Lin, Hongmei; Zhang, Miao; Qu, Changhai; Yan, Lei; Yin, Xingbin; Ni, Jian (Frontiers in Pharmacology, 2017)
Herbal medicine has been widely used in the treatment of various diseases; however, the adverse reactions cannot be ignored. Most previous studies have ignored the relationship between the factors of geographical areas/batches and toxicity. This study used Polygonum multiflorum (PM) as an example to analyze the relationship between the geographical areas/batches and toxicity and speculated on the hepatotoxicity-inducing components in PM based on high content screening, UHPLC-Q-TOF/MS and Progenesis QI software analysis. The results of the study show that the toxicity of PM was obviously different among the different geographical areas, and the most toxic PM was from the Sichuan province. To obtain more accurate results and to reduce the false-positive rate, two methods were used to evaluate the speculative results. It was noteworthy that emodin was not the main hepatocyte toxicity constituent of PM. The analysis methods suggested that PM toxicity may be associated with tetrahydroxystilbene-O-(galloyl)-hex and emodin-O-hex-sulphate. The toxicity of these two components requires further study.